How the internet increases modern contraception uptake: evidence from eight sub-Saharan African countries - Veronica Toffolutti; Hai Ma; Giulia Menichelli; Ester Berlot; Letizia Mencarini; Arnstein Aassve (BMJ Global Health, 2020)
Background Sub-Saharan African (SSA) countries have the highest worldwide levels of unmet need for modern contraception. This has led to persistently high fertility rates in the region, rates which have had major adverse repercussions on the development potential there. Family planning programmes play a key role in improving the uptake of modern contraception, both by fostering women’s health and by lowering their fertility. Increasing awareness of contraception benefits is a major component of such programmes. Here, we ask whether internet access can bridge the gap between women’s need for modern contraception and women’s uptake of the same.Methods We use a compendium of data for 125 242 women, aged 15–49, from the Demographic Health Survey, Akamai and International Communication Union data, covering eight SSA countries, for the period 2014–2019. We apply a Two-Stage Least Square model, using as instruments for individual internet exposure the distance to the main server in the country and whether the backbone network in the country has been connected to at least one submarine cable.Results Internet exposure, measured as women access the internet at least monthly (almost daily), is associated with a positive, 11.4% (95% CI 10.6% to 12.2%) (53.8% (95% CI 13.4% to 94.1%)), increase in modern contraception uptake. Education is an important moderator. Poorly educated women benefit the most from internet exposure.Discussion Internet exposure appears to have significantly increased the uptake of modern contraception among sub-Saharan women. The poorly educated appear particularly to benefit. There are two mechanisms at play: the internet increases women’s knowledge of contraception; and, in parallel, fosters their empowerment.